Approaches used by Police Officers Towards Maladaptive Behaviors of Law Offenders in the First District of Camarines Sur - Paredes, Emmarie (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the approaches used by police officers in dealing with maladaptive behaviors of law offenders in the First District of Camarines Sur and proposed an intervention program to enhance these approaches. It was anchored on Procedural Justice Theory, Social Learning Theory, Social Cognitive Theory, and Rational Choice Theory, which explain police behavior, decision-making, and interactions with law offenders. A descriptive-comparative research design was employed involving 116 police officers from five municipalities in the First District of Camarines Sur. Data were collected using a validated researcher-made questionnaire and analyzed using frequency count, percentage, weighted mean, ranking, and one-way analysis of variance (ANOVA). The findings revealed that the respondents were predominantly middle-aged male Police Non-Commissioned Officers with college degrees and moderate years of service. Among the maladaptive behaviors encountered, disinhibition was the most prevalent, followed by antagonism and detachment, all of which were observed to a neutral extent. Police officers frequently applied appropriate approaches in managing these behaviors, particularly those emphasizing respectful communication, procedural fairness, emotional regulation, conflict management, and de-escalation. Significant differences in the approaches used were found according to sex, educational attainment, civil status, position/rank, and years in service, while age showed no significant difference. Based on these findings, a three-year intervention program was proposed to strengthen police officers’ competencies through continuous professional development and evidence-based policing strategies. This study supports Sustainable Development Goal (SDG) 16: Peace, Justice and Strong Institutions by promoting ethical, accountable, and effective policing, and SDG 3: Good Health and Well-Being by encouraging safe and humane interactions between police officers and law offenders. The findings contribute to institutional, governance, community, and public safety sustainability by providing evidence to improve police training, strengthen community trust, and support evidence-based law enforcement practices.